Myeloid‐derived suppressor cells induce regulatory T cells in chronically HBV infected patients with high levels of hepatitis B surface antigen and persist after antiviral therapy. Issue 10 (15th April 2019) - Pal, Sourina; Nandi, Madhuparna; Dey, Debangana; Chakraborty, Bidhan Chandra; Shil, Achintya; Ghosh, Saurabh; Banerjee, Soma; Santra, Amal; Ahammed, S. K. Mahiuddin; Chowdhury, Abhijit; Datta, Simanti
Summary: Background: CD4 + regulatory T‐cells (Tregs) expand during chronic hepatitis B virus (HBV) infection and inhibit antiviral immunity, although the underlying mechanism remains largely elusive. Myeloid‐derived suppressor cells (MDSC) have been linked with T‐cell dysfunction but questions remain regarding their persistence/profile/function in chronically HBV infected patients. Aim: To characterise MDSC in different phases of chronic HBV infection namely, immune‐tolerant (IT), hepatitis B e‐antigen‐positive chronic hepatitis B (EP‐CHB), inactive carriers (IC) and hepatitis B e‐antigen‐negative chronic hepatitis B (EN‐CHB), to investigate their role in Treg induction and evaluate the effect of anti‐viral therapy on these cells. Methods: Multiparametric flow cytometry, cell‐sorting and co‐culture assays were performed along with longitudinal immune monitoring of CHB patients receiving tenofovir. Results: HLA‐DR ‐ CD11b + CD33 hi ‐Monocytic‐MDSC (M‐MDSC) were enhanced in IT, EP‐CHB and EN‐CHB compared with IC, and this was related to increasing hepatitis B surface antigen (HBsAg) concentration. IT and EP‐/EN‐CHB displayed elevated frequency of CD4 + CD25 + FOXP3 + Treg that positively correlated with that of M‐MDSC. However, both M‐MDSC and HLA‐DR ‐ CD11b + CD33 low ‐granulocytic‐MDSC from IT and EP‐/EN‐CHB expressed high transforming growth factor beta (TGF‐β) and interleukin‐10 (IL‐10). Co‐culture of sorted HLA‐DR ‐ CD33 + ‐MDSC with autologous MDSC depleted‐PBMC from IT and CHB but not from IC, increased CD4 + CD25 + FOXP3 + ‐iTreg and CD4 + FOXP3 ‐ IL‐10 + ‐Tr1‐cells through a cell‐contact independent mechanism. While MDSC‐derived TGF‐β and IL‐10 promoted development of iTreg, only IL‐10 appeared to be crucial for Tr1 induction. One year of tenofovir treatment failed to normalise MDSC frequency/function or reduce Treg percentage and serum HBsAg levels, despite reduction in viral load. Conclusions: We established a previously unrecognised role of MDSC in Treg development in IT and EP‐/EN‐CHB via TGF‐β/IL‐10‐dependent pathways and both cell‐types persisted after anti‐viral therapy. Hence, therapeutic targeting of MDSC or reducing circulating HBsAg level together with tenofovir‐therapy might be more effective in restricting HBV persistence and disease progression.